Bipolar Disorder in pediatric patients: a nationwide retrospective study from 2000 to 2015 - André Sá Padrão Gameiro Campos (2021)
Objective: Pediatric bipolar disorder (PBD) has been the focus of increased attention mainly due to controversies surrounding its diagnosis and prevalence. To date, in Portugal, there is no evidence available for nationwide PBD-related hospitalization rates. This study aimed to describe and characterize all pediatric hospitalizations with a primary diagnosis of bipolar disorder (BD) registered in Portugal from 2000 to 2015. Methods: A retrospective observational study was conducted. Pediatric (<18 years) inpatient episodes with a primary diagnosis of BD were selected from a national administrative database containing all hospitalizations from Portuguese mainland public hospitals. The ICD-9-CM codes 296.x (excluding 296.2x, 296.3x and 296.9x) were used to identify the diagnosis of interest. Additionally, age at discharge, sex, psychiatric comorbidities, length of stay (LoS), admission type and date, in-hospital mortality and hospital charges were analyzed. Results: A total of 348 hospitalizations, representing 258 patients, were identified. The overall population-based rate of hospitalizations was 1.18/100.000 youths. A non-linear increase throughout the study period was found. Patients were mostly female (60.60%), with a median age of 16 years (Q1-Q3:14-17). Admissions were mostly urgent (81%), and the median LoS was 14 days (Q1-Q3:7-24). Moreover, 26% of all episodes were readmissions. Mean estimated charges per episode were 3503.10€, totalizing 1.20M€. Conclusions: Annual rates of PBD hospitalizations showed a non-linear increase. These findings may contribute to better understand the PBD burden. Nevertheless, more research is warranted, to better characterize sociodemographic and clinical trends in PBD to prevent the high number of acute hospitalizations and readmissions of these patients.